The New Politics of Surveillance and Visibility - Haggerty, Kevin D.; Ericson, Richard V., 1948-2007 (Book collections on Project MUSE., 2006)
This collection challenges conventional wisdom and advances new theoretical approaches through a series of studies of surveillance in policing, the military, commercial enterprises, mass media, and health sciences.